(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract Breastfeeding problems that can arise from the first day to the third day postpartum is ASI not streamlined. ASI does not streamlined make the mother unable to meet the needs of the baby. The purpose of this study was to determine the effect of a combination of the technique marmet and warm compresses on milk production. The study was conducted in August 2019 until April 2020 in PMB Dince Safrina City of Pekanbaru. This type of research is quantitative research using a Quasi Experiment design. The population in this study were all postpartum mothers in January-February 2020 who delivered at PMB Dince Safrina totaling 27 people. The sample in this study were 20 postpartum mothers taken with incidental sampling technique. Data collection uses the observation method using an observation sheet. Data analysis used independent t test with a significance level of 95%. The results showed that the average milk production in the combination intervention group was 107.00 ml (SD 22.63) compared to the marmet technical intervention group which was 77.00 ml (SD 27.10). The conclusion of the study is the influence of the technique of marmet with and without warm compresses on milk production in postpartum mothers (p = 0, 015), it intended the combination of marmet technique and warm compresses is more effective in increasing milk production. The advice given is that a combination of the marmet technique and warm compresses can be applied in midwifery care for postpartum mothers to help increase and expedite milk production.